Contribution Of Limb Length And Brick Flexibility to Smash Ability In Volley Balls Lueng IE Aceh Big White Elang - Syamsulrizal, Syamsulrizal; Iqbal, Muhammad; Zahara, Zahara (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. This study aims to study and find out this method is used to obtain information directly from informants regarding